Recent advances in the crosstalk between the brain-derived neurotrophic factor and glucocorticoids - Tsimpolis, Alexandros; Kalafatakis, Konstantinos; Charalampopoulos, Ioannis (Frontiers in Endocrinology, 2024)
Brain-derived neurotrophic factor (BDNF), a key neurotrophin within the brain, by selectively activating the TrkB receptor, exerts multimodal effects on neurodevelopment, synaptic plasticity, cellular integrity and neural network dynamics. In parallel, glucocorticoids (GCs), vital steroid hormones, which are secreted by adrenal glands and rapidly diffused across the mammalian body (including the brain), activate two different groups of intracellular receptors, the mineralocorticoid and the glucocorticoid receptors, modulating a wide range of genomic, epigenomic and postgenomic events, also expressed in the neural tissue and implicated in neurodevelopment, synaptic plasticity, cellular homeostasis, cognitive and emotional processing. Recent research evidences indicate that these two major regulatory systems interact at various levels: they share common intracellular downstream pathways, GCs differentially regulate BDNF expression, under certain conditions BDNF antagonises the GC-induced effects on long-term potentiation, neuritic outgrowth and cellular death, while GCs regulate the intraneuronal transportation and the lysosomal degradation of BDNF. Currently, the BDNF-GC crosstalk features have been mainly studied in neurons, although initial findings show that this crosstalk could be equally important for other brain cell types, such as astrocytes. Elucidating the precise neurobiological significance of BDNF-GC interactions in a tempospatial manner, is crucial for understanding the subtleties of brain function and dysfunction, with implications for neurodegenerative and neuroinflammatory diseases, mood disorders and cognitive enhancement strategies.